Powder technology handbook. - Masuda, Hiroaki, 1943-; Higashitani, Kō, 1944-; Yoshida, Hideto, 1952- (Taylor & Francis, 2006)
Continuing the tradition of the bestselling Powder Technology Handbook, this definitive source examines the fundamental engineering processes of particulate technology. Combining several sections for easier reference, the third edition has been updated and expanded by nearly 30% to reflect recent advances. The authors have added new sections on particle motion in fluid, design and formulation of composite particles, combustion and heating, electrostatic powder coating, attrition of a particle, breakage of aggregates, particle motion in a powder bed, and rheological and electrical properties of a powder bed. The book also discusses newly developed areas such as simulation, surface analysis, and nano-particles.